1998
DOI: 10.1021/op980029b
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Seeding Technique for the Crystallization of the Metastable A Modification of Abecarnil

Abstract: Abecarnil, a partial agonist of the benzodiazepine receptor, crystallizes in three modifications, A, B, and C. Depending on the solvent, the form crystallized in an unseeded process is one of the two metastable forms A or B. Isopropyl acetate was chosen as solvent for the crystallization of the drug substance Abecarnil, yielding the B form for an unseeded crystallization. However, the crystals undergo a slow solution-mediated phase transformation into the stable C form. More readily observed is a partial phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 11 publications
0
55
0
Order By: Relevance
“…This sudden appearance of ''first crystals'' is described in the literature as an avalanche [5] or showers of crystals [6]. However, it is questionable whether such crystals are really the first ones or not.…”
Section: Introductionmentioning
confidence: 99%
“…This sudden appearance of ''first crystals'' is described in the literature as an avalanche [5] or showers of crystals [6]. However, it is questionable whether such crystals are really the first ones or not.…”
Section: Introductionmentioning
confidence: 99%
“…The well known Ostwald's rule of stages [5] predicts that the least stable form is produced first by spontaneous crystallization and then transforms into the more stable form. Ostwald's rule of stages rule has, however, no general proof in industrial practice, and the form of the crystals depends on the crystallizing system and the operation parameters, such as solvent, temperature range, supersaturation level, mixing condition, presence of impurities or additives, and seeding parameters [6][7][8][9]. The well known historical case about Ritonavir has shown that insufficient understanding of the crystallization mechanisms of the polymorphs could cause serious problems in drug manufacturing [10].…”
Section: Introductionmentioning
confidence: 99%
“…2a and b. This kind of particle increasing trend has been reported in actual crystallization experiments as an avalanche [25] or showers of crystals [26]. The avalanche or showers of crystals have been treated incorrectly as the appearance of ''first crystals'', as pointed out in the previous paper [21].…”
Section: Trend Of the Number Density Of The Total New Crystalsmentioning
confidence: 95%